Survey on the conservation and use of forest genetic resources in Latin America - Salcedo, J.; Baena, M.; Scheldeman, X.; Vinceti, B.; Willemen, L. (Forest Systems, 2009)
In order to understand the state of conservation and use of forest genetic resources in Latin America, an on-line survey of forestry personnel and organizations was conducted in 2006. Most respondents work on forestry, agroforestry and human-resource development, at national government organizations and universities. Research is local and focuses on developing agroforestry systems and on production and propagation trials. The top problems identified are the lack of funds, policies and recognition of the importance of forest genetic resources. According to the respondents, it is necessary to set priorities for work, define species of common interest, and work collaboratively to optimize resources. Professionals also lack information resources and mechanisms to communicate with peers, and recommended the creation of a regional network of specialists.